Análise biopsicossocial na sociedade de risco global como dispositivo da efetividade e garantia dos benefícios por incapacidade - Bonetti, Débora Patrícia Rosa (2021)
This is the present demonstration of the importance of social protection for people who are at social security risk of labor incapacity, especially those of the 21st century, known as “global risk”. Thus, the expert system that today strictly makes a biomedical analysis of the individual, needs to evolve to an inter and multidisciplinary analysis, considering social, economic, cultural, technological, work history, among others. We highlight the recent pandemic of Covid-1919 and the adoption of social, health, education, health, social security and other policies, such as, for example, the emergency measure of granting temporary disability benefits, using the biopsychosocial criterion in the degree higher – the one that waives the physical examination of the insured. Social risk represents the ambivalence and complexity of postmodernity, reflected in the disrepute of society's ability to manage risks and sponsor protection mechanisms. For this reason, traditional instruments of social protection, such as social security in its various aspects, should not be abandoned, but should be revised, in order to ensure, in the face of social change, better support for those who need it. It is concluded in this bias, by researching a living object, changeable and changeable under the internal and external influences, which does not constitute a simplified undertaking, but necessary to supply the deficiencies of the social security institution and increase the reach to welfare and social justice, as an alternative, if not the best of them, the adoption of biopsychosocial expertise in an effective, regulated and comprehensive way, since it conducts the pathological and psychosocial study, thus achieving social justice anchored in ethical, moral and social principles, tutored in our legal system